2016
DOI: 10.11138/ccmbm/2016.13.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Natural mineral waters: chemical characteristics and health effects

Abstract: SummaryWater contributes significantly to health and a daily intake of 1.5 to 2 liters of water should be guaranteed, because a good hydration is essential to maintain the body water equilibrium, although needs may vary among people. However, worldwide population is far from the Recommended Allowance for water intake. Among the waters for human uses, there are 'waters (treated or not), intended for drinking, used for the food and beverages preparation or for other domestic purposes' and natural mineral waters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 42 publications
1
121
0
3
Order By: Relevance
“…as shown in Table 1. These results indicated that Phusang hot spring should be classified as low mineral content water (Quattrini et al, 2017). The sodium is <20 mg/L and this is indicated as a low sodium definition (Quattrini et al, 2017).…”
Section: Resultsmentioning
confidence: 87%
“…as shown in Table 1. These results indicated that Phusang hot spring should be classified as low mineral content water (Quattrini et al, 2017). The sodium is <20 mg/L and this is indicated as a low sodium definition (Quattrini et al, 2017).…”
Section: Resultsmentioning
confidence: 87%
“…Bicarbonate waters create an alkaline environment and decrease bone resorption. They also have some benefits in reducing total cholesterol, LDL cholesterol, and fasting glucose [23].…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 99%
“…Sulphates (generally magnesium, sodium or calcium sulphate) are present in mineral water with concentration that can be higher than 200 mg/L in 'sulphate-rich' mineral water (Casado et al, 2015;Quattrini et al, 2016).…”
Section: Exposure Via Other Sourcesmentioning
confidence: 99%